Heart Failure in Humans: Mitochondrial Structure and Function - Shodiyev Mirshodbek Marufovich, (American Journal of Biology and Natural Sciences, 2025)
Despite clinical and scientific advancements, heart failure is the major cause of morbidity and mortality worldwide. Both mitochondrial dysfunction and inflammation contribute to the development and progression of heart failure. Although inflammation is crucial to reparative healing following acute cardiomyocyte injury, chronic inflammation damages the heart, impairs function, and decreases cardiac output. Mitochondria, which comprise one third of cardiomyocyte volume, may prove a potential therapeutic target for heart failure. Known primarily for energy production, mitochondria are also involved in other processes including calcium homeostasis and the regulation of cellular apoptosis. Mitochondrial function is closely related to morphology, which alters through mitochondrial dynamics, thus ensuring that the energy needs of the cell are met. However, in heart failure, changes in substrate use lead to mitochondrial dysfunction and impaired myocyte function. This review discusses mitochondrial and cristae dynamics, including the role of the mitochondria contact site and cristae organizing system complex in mitochondrial ultrastructure changes. Additionally, this review covers the role of mitochondria-endoplasmic reticulum contact sites, mitochondrial communication via nanotunnels, and altered metabolite production during heart failure. We highlight these often-neglected factors and promising clinical mitochondrial targets for heart failure.